Evaluation of the forum theatre approach for public engagement around antibiotic use in Myanmar. - Myo Maung Maung Swe; Phyu Hnin Hlaing; Aung Pyae Phyo; Htet Htet Aung; Frank Smithuis; Elizabeth A Ashley; Phaik Yeong Cheah (PLoS ONE)
Introduction The risk of emergence and spread of antibiotic resistance is high in Southeast Asian countries and various strategies are being used to raise awareness about appropriate antibiotic use and antibiotic resistance within communities. Public engagement in science has not been widely practised in Myanmar. We describe the use of a forum theatre to engage with the community about antibiotic use. Methods The engagement activities took place in a peri-urban township in Yangon, Myanmar. Five preliminary story gathering workshops with the community were carried out to develop scripts and songs for the forum theatre. After that, we organised forum theatre plays between September and October 2018. Following each play we provided four simple key messages based on WHO's world antibiotic awareness week advocacy materials; 1) Antibiotics are medicines used to treat bacterial infections 2) Antibiotics are not useful for coughs and colds 3) Never use leftover antibiotics or share antibiotics with others 4) Prevent infections by regularly washing hands, preparing food hygienically, avoiding close contact with sick people, and keeping vaccinations up to date. We evaluated the engagement activities by conducting focus group discussions (FGD) with audience members. Results Ten forum theatre plays were performed on two topics; "Fever and antibiotics" and "Mixed medicines", reaching 1175 community members. Four themes emerged from our thematic analysis: 1) Knowledge dissemination, 2) Enjoyment and fun, 3) Willingness to support and recommendations for future engagement activities and 4) Preference over traditional methods of health education. We found improvement of antibiotic related knowledge and enjoyment among audience who were also willing to support future engagement activities and preferred forum theatre approach over formal health talks. Conclusions We conclude that forum theatre is an effective innovative approach to engage and disseminate knowledge on appropriate use of antibiotics with the community in a participatory way.